Clinical outcomes of HeartMate 3 left ventricular assist device support with a Bridge to Transplant vs a Destination Therapy strategy: a single-centre retrospective cohort (Swiss Medical Weekly, 2024)
INTRODUCTION: Real-world outcomes with the HeartMate 3 left ventricular assist device (LVAD) depending on whether it’s a bridge to transplantation (BTT) or destination therapy (DT) are poorly studied. We aimed to compare the profile and clinical outcomes of patients supported with HeartMate 3 according to a BTT or a DT pre-implantation strategy.METHODS: All patients consecutively implanted with HeartMate 3 at our centre (University Hospital of Lausanne, Switzerland) in 2015–2022 were analysed in a retrospective observational study. Indications for HeartMate 3 implantation were advanced heart failure despite optimal medical treatment. Patients were treated with a vitamin K antagonist anticoagulant combined with antiplatelet therapy after HeartMate 3 implantation and were followed up monthly at our institution.RESULTS: Among 71 patients implanted with HeartMate 3 between 2015 and 2022, 51 (71.8%) were implanted as a BTT and 20 (28.2%) as DT. Their median age was 58 (IQR: 52–69) years and 84% of patients were classified as INTERMACS profiles 2–4. The median follow-up duration was 18.3 (IQR: 7.5–33.9) months. Patients in the DT group were older than those in the BTT group (p